A bionic mechanical foot with adaptive variable postures travelling on sand. (June 2023) - Zhang, Rui; Sun, Xumin; Han, Dianlei; Zhang, Rui; Zhang, Hua; Ma, Jia; Wen, Lige; Zou, Meng
Highlights: Bionic mechanical foot can realize the conversion of different postures during the touchdown period. Speed and medium of action affect the travelling and traction performance of the bionic mechanical foot. Variable posture bionic mechanical feet are suitable for movement at higher speeds on sandy surfaces. Abstract: In this study, an adaptive variable posture bionic mechanical foot is designed, which enables the transformation of different postures during the touchdown period. At the same time, the bolts at the joints are tightened to enable the non-variable configuration function of the bionic mechanical foot. A test rig was used to test the travelling and traction performance of the bionic mechanical foot at different speeds on sandy and hard surfaces. The results show that on sandy surfaces, at both high and low speeds, the variable posture mechanical foot outperforms the non-variable posture mechanical foot, especially at high speeds, indicating that the variable mechanical foot is suitable for movement at higher speeds on sandy ground. On hard ground, the traction and pedaling forces generated by the variable posture mechanical foot are essentially the same as those generated by the non-variable posture mechanical foot at low and high speeds, indicating that the travelling and traction performance of both mechanical feet on hard ground is the same. The variable posture mechanical foot is suitable for high-speed movement on sandy ground, providing a theoretical and technical basis for the design of future legged robots for efficient movement on desert surfaces and deep space soft surface environments.